2012
DOI: 10.1177/0018720812438614
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Efficacy of an Ergonomics Program That Includes Patient-Handling Devices on Reducing Musculoskeletal Injuries to Nursing Personnel

Abstract: Implementation of patient-handling devices along with a comprehensive program can be effective in reducing MSDs among nursing personnel. Strategies to expand usage of patient-handling devices in most health care settings should be explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
126
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(129 citation statements)
references
References 53 publications
1
126
0
2
Order By: Relevance
“…Compared with data from the US, Australia, and Canada, which often report yearly prevalences of musculoskeletal injuries >20%, this number seems quite low (15)(16)(17), even though within the US there are large differences in injury claims across studies (26). Such differences may to a large extent be explained by differences in case definitions and reporting behaviors.…”
Section: Occurrence Of Back Injurymentioning
confidence: 72%
See 3 more Smart Citations
“…Compared with data from the US, Australia, and Canada, which often report yearly prevalences of musculoskeletal injuries >20%, this number seems quite low (15)(16)(17), even though within the US there are large differences in injury claims across studies (26). Such differences may to a large extent be explained by differences in case definitions and reporting behaviors.…”
Section: Occurrence Of Back Injurymentioning
confidence: 72%
“…This supports results from Australian and US studies showing up to 44% reduced numbers of back injury claims after implementation of "no lifting" or "minimal manual lifting" policies, eg, by using assistive devices during patient transfer (15,16). In a study by Garg and Kapellusch (17), a more comprehensive participatory ergonomics program -including several aspects such as a "no manual lifting" policy, management commitment, empowering ergonomics teams in selection and use of equipment, program training, compliance, and continuous improvement -in seven nursing facilities in the US resulted in 60% fewer patient-handling injuries 2-5 years later (17). An observational study across 23 US states showed that safe lift programs in healthcare facilities -endorsed and promoted by directors of nursing -reduced injury compensation claims frequency and costs (28).…”
Section: Use Of Assistive Devices and Risk Of Back Injurymentioning
confidence: 99%
See 2 more Smart Citations
“…Such injuries often result in significant lost work time, and could lead to low morale in workplace. While best practices in patient handling are known, training alone has proven ineffective due to the lack of compliance in actual practice [16], [17]. In this project, we aim to develop a low-cost real-time monitoring and feedback system to enhance the workers' compliance to best practices.…”
Section: Discussionmentioning
confidence: 99%